Dagbani Wikipedia Bachinima - Shahadu, Sadik; Abdulai, Mohammed Sadat (Septentrio Conference Series, 2021)
First, Sadik and Sadat will take participants through their experiences in supporting the Dagbani Wikipedia community and the challenges they face. The focus of this session will provide general information on how tools like the Spell4Wiki app can help: Provide support for indigenous language Wiktionaries Add audio recordings of words to Wikipedia articles Describe items on Wikidata; e.g. Q98185154#P443 or Q105#P443 provide support for Wikidata:Lexicographical data Help application developers to reuse the content in building their tools, etc We will introduce participants to the Spell4wiki app, and how they can create audio recordings of words in their native languages on Wikimedia Commons.